The benefits of rural roads : enhancing income opportunities for the rural poor - Escobal, Javier (2002)
Most studies have measured the benefits of rehabilitated rural roads by focusing on reductions in monetary or time costs needed to access product and factor markets or key public social services. This paper complements these studies by evaluating their impact on key welfare indicators such as income or consumption. Looking at rural households living in some of the poorest districts of Peru, this study compares (using propensity score matching techniques) households located near rehabilitated roads to suitable controls. Results show that rehabilitated road accessibility can be related to changes in income sources, as the rehabilitated road enhances non-agricultural income opportunities, especially from wageemployment sources. The study also finds that income expansion is not been matched by an equivalent consumption increase; apparently because the additional income is allocated to savings, through increments in livestock, most likely because road quality improvement is being perceived as transitory.